PENGARUH PEMBERIAN MACAM MEDIA DAN MACAM URIN TERHADAP HASIL TANAMAN STROBERI (Fragaria ananassa) - Arif Rifai; Hadi Rianto; Yulia Eko Susilowati (JURNAL VIGOR, 2018)
The research is to study the effect of kind of media and the effect of kind of urine to the strawberry yield (Fragaria ananassa). The experiment was done in 10 October 2016 until 29 Desember 2016. Location of experiment is in Sumber, Dukun, Magelang. The altitude is 660 m. The soils is regosol with pH 6,3. The research method used factorial experiment (3x3) arranged in a randomized complete block design with three replications. The first factor is kind of media goat manure, compost, rice husk. The second factor is kind of goat urine, rabbit urine and cow urine. The result of the research show that the use of kind of goat manure media shortened flowering age, icreases number of flower, weight of fruit, fresh weight of stover and leaf width. Compost manure increases weight of fruit and leaf width. Rabbit urine increases number of flower, number of fruit and weight of fruit. The combination of compost media and goat urine accelerate flowering age.